Study of Cypermethrin induced puff in Sarcophaga Ruficornis (FAB.) (Sarcophagidae: Diptera) - AKANKSHA SINGH; RASHMI SINGH (International Journal of Pharma and Bio Sciences, 2018)
To assess the survival of the cell, response against insecticide cypermethrin in organism can lead to changes in puffing activity at chromosomal level. The cytogenetic approach is an economical, quick and valuable tool that can be used with various sarcophagid species. Cypermethrin treatment in the present study evoked the induction of a single puff at locus 12A of chromosome arm IIL in Sarcophaga ruficornis. This response is similar to the stress response in Sarcophaga bullata and oher species of Sarcophaga. It is interesting to note that in all the species of sarcophagids the puff is induced at the region homologous to 12A of IIL arm which is characterized by identical banding pattern and reveals that, there has been conservation of the region in the terms of banding pattern. The flesh flies belonging to the genus Sarcophaga are endowed with good quality polytene chromosomes in the nuclei of dorsal foot pad cells. Thus, one has opportunity to examine the response of stress at the cytological level in the sarcophagid flies. In the present study, it is proposed to carry out a cytological analysis of the polytene chromosomes to identify the chromosomal loci responsive to the insecticide cypermethrin.Cypermethrin induces a single puff on chromosome arm IIL at the region 12A by in vitro treatment. Several studies, have demonstrated that under stressful conditions, cells from all living organisms respond by a cascade of events referred to as “heat shock” or “stress response”.In the unstressed cells, these activities have constitutive functions that are essential in various aspects of protein metabolism. The highest level of puffing activity was detected in Sarcophaga ruficornis population with high concentrations of insecticide in the acetone solution. In pupae from treated group, a key structure of the foot pad chromosome sharply increased their puffing activity to levels up those observed normal conditions. It is concluded that Puffing activity in the polytene chromosomes can be used as tools for evaluating the genotoxicity of the environment.